Tata Kelola Perusahaan Yang Baik, Manajemen Risiko Dan Kinerja Keuangan Di Bank Syariah - Aminudin Aminudin (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
The syariah banking follows the Islamic law making its cultural background very different to the conventional banking. There is tight competition between the two banking systems in providing customer’s expectation with the best quality of customer service. To allow the syariah banking to win the competition against conventional banking, it is important to have the finest product strategy and quality service scheme in place. This research is using Multiple Regression analysis, resulting in four dimensions of quality service.They are assurance, reliability, tangible and empathy. These dimensions can influence positive customer’s satisfaction. Other dimension such as compliance cannot have positive influence on customer’s satisfaction. Statistically that not all variable of quality services demonstrate significant result. Dimension variable that demonstrates significant result is assurance, reliability, tangible and empathy, while compliance and responsiveness does not have significant result and only reach the confidence rate of 95%.